Exploring young consumer's understanding of local food through proximity and social representations - László, Veronika; Wahlen, Stefan (Frontiers in Sustainable Food Systems, 2024)
The ever-changing nature of consumers' understanding of local food highlights the need for in-depth research. This study explores how Gen-Z consumers define, perceive and experience local food. Through the analysis, we extend the existing conceptualisation of local food by differentiating three aspects of proximity: geographical, value, and relational proximity. We contribute novel insights into the differentiation of proximity to the established understanding for this specific consumer group. Methodologically, we use a free association game played with Gen-Z consumers in Hungary. Theoretical frameworks, including social representation, central core and proximity theories, are used to uncover implicit knowledge about local food. The results reveal a consumer understanding that associates health, freshness, taste, quality and trustworthiness as the central core of the local food concept. Surprisingly, value and relational proximity gain importance, while geographical proximity takes a peripheral role. This study facilitates a re-evaluation of the local food concept in light of evolving consumer understanding, while also establishing a link between proximity theories and social representation theory. The findings provide practical implications that distinguish different aspects of proximity that are relevant to farmers and policy makers in light of evolving consumer understandings.